Trade Liberalization And Poverty In West African Countries: Feasible Generalized Least Square Method Analysis - OLUWO, Peter Olugbenga; ORESAJO, Adegbenga Safiriyu (International Journal of Economics and Development, 2025)
: The study investigates the effect of trade liberalisation on poverty reduction in West African countries, with particular reference to ECOWAS member states, in order to determine whether increased openness enhances welfare and reduces poverty across the region. Using annual panel data for 15 countries spanning 1990–2022, the study employs the Feasible Generalized Least Squares (FGLS) estimation technique to account for cross-sectional dependence, heteroskedasticity, and serial correlation. Descriptive statistics, correlation analysis, and diagnostic tests such as the Variance Inflation Factor (VIF) and Pesaran tests confirmed the reliability and stationarity of the data. Empirical results reveal that trade liberalisation exerts a significant negative effect on poverty, implying that greater trade openness reduces poverty levels across West Africa. Exchange rate stability and institutional quality were also found to have strong negative relationships with poverty, while inflation exhibited a positive effect, indicating its adverse impact on welfare. The findings support the Solow growth model, which links openness to economic expansion and poverty reduction through productivity gains and technological diffusion. The study concludes that while trade liberalisation contributes to poverty alleviation, its benefits remain uneven due to weak institutions and infrastructural constraints. It recommends that West African governments pursue inclusive trade policies supported by sound macroeconomic management, institutional reforms, and targeted investments in human capital and rural development to ensure that the gains from liberalisation translate into broad-based poverty reduction.